THE BENDING CAPACITY OF CONCRETE BEAM DUE TO ADDITION OF IRON FIBER (WASTE OF LATHE MACHINE) - Samuel Layang; Wiratno (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
This research aimed to determine the effect of iron fibers (waste of lathe machine) to the capacity of flexure in normal concrete mix. This research uses test specimen of 15 pieces cylindrical (size 15 cm x 30 cm) and 9 lengths of beam (length x width x height: 60 cm x 15 cm x 15 cm). Concrete mix are designed complying to SNI 03-2834-2000 on Procedures Mix Concrete Manufacturing Plan for Normal. Concrete cylinders were tested at 28 days to get the actual compressive strength. Concrete beams were tested based on ISO 4431:2011 test method for flexural strength of normal concrete by two point loading at 28 days to obtain a flexural strength, fracture patterns that occur. Based on the test results of concrete cylinders, the average value of compressive strength for each variation of the mixture is 14.58 MPa (fiber content 0%); 10.80 MPa (fiber content 8%); 13.60 MPa (the fiber content of 10%). Flexure testing results for each variation of the mixture was 1.87 MPa (fiber content 0%); 1.64 MPa (fiber content 8%); 1.78 MPa (fiber content 10%). The pattern of cracks that occur in all the beams show the same results that the crack caused by the bending effect. Cracks occurred in the middle of the beam span that starts from the bottom side experiencing gravity and move toward the top and finish with the breaking of the beam.